PELATIHAN Pemasaran Digital Dasar DALAM UPAYA PERCEPATAN PENGEMBANGAN UMKM di SMK ASGA MANDIRI - Ari Usman; Fitri Annisah lubis, Yessi; Dedy Irwan; Liza Fitriana; Yuyun Dwi Lestari; Sarudin; Arief Budiman; Dodi Siregar; Edy Rahman Syahputra; Nur Wulan; Divi Handoko (Jurnal Pengabdian Masyarakat, 2023)
Training for teachers and MSMEs at Asga Mandiri Vocational School with the theme Basic Digital Marketing was carried out to increase teachers' and MSMEs' understanding of basic digital marketing. The methodology used in this service is to present material regarding basic digital marketing. Next, provide a tutorial to the participants and evaluate how they understand the material that has been tutorialized using digital platforms such as Google Business and WhatsApp Business. The evaluation results of this activity show that the training is effective in increasing the understanding of teachers and MSMEs so that it can be used as a medium in the business development process, for promotion and product sales. Basic digital marketing training is very important for teachers and MSMEs because it can improve their ability to carry out marketing activities via digital platforms.